145k views
1 vote
Solve the system of equations below using elimination by addition.3m - n = 11m - 3n = -15

User Luke Smith
by
4.8k points

1 Answer

6 votes

Given the following System of equations:


\begin{cases}3m-n=11 \\ m-3n=-15​\end{cases}

You can solve it using the Elimination method as following:

1. You can multiply the first equation by -3.

2. Add the equations.

3. Solve for the variable "m".

Then:


\begin{gathered} \begin{cases}-9m+3n=-33 \\ m-3n=-15​\end{cases} \\ ------------ \\ -8m=-48 \\ \\ m=(-48)/(-8) \\ \\ m=6 \end{gathered}

4. Substitute the value of "m" into any original equation.

5. Solve for the variable "n".

Then:


\begin{gathered} 3m-n=11 \\ 3(6)-n=11 \\ 18-n=11 \\ n=11-18 \\ n=-7 \end{gathered}

The solution is:


\begin{gathered} m=6 \\ n=-7 \end{gathered}

User Little Pootis
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.